Perancangan Sistem Informasi Pemesanan Spectrum Party Planner Dengan Menggunakan Metode AHP - Desi, Efani (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Wedding Organizer is a service that works personally to help the bride and groom in planning and supervision of the implementation of the wedding party by schedule and budget that have been set. Wedding organizer information system created using web-based information technology to expand the area of promotion and sale of wedding packages and simplify the ordering process. System Design Information Ordering Wedding Organizer is UML modeling visualization (Unified Modeling Language), and this application applies the method Analytical Hierarchy Process (AHP), namely by weighting the criteria and vendors. The programming language used is the PHP programming language (PHP Hypertext Preprocessor) with MySQL as the Database Management System (DBMS), and Atom as an editor. A wedding organizer information system is very helpful for people who do not want to bother with their wedding planning issues. With the development of technology today, the wedding Organizer has begun to move from the manual process into the online process of the wedding information system-based organizer web.